Temperature Variability over the Po Valley, Italy, according to Radiosounding Data - Boyan Hristozov Petkov (Advances in Meteorology)
Temperature variations registered above the southeast part of the Po Valley, Italy, have been examined by applying the principal component analysis of radiosounding profiles recorded during the period from 1987 to 2010. Two datasets, considered to describe intra- and interannual oscillations, respectively, were extracted from the measurements data and the results show that both types of fluctuations can be projected onto four empirical orthogonal functions (EOFs), interpreted as vertical distributions of oscillation amplitudes and four uncorrelated time series that represent the evolution of corresponding EOFs. It was found that intra-annual oscillations composed of periods between 30 and 120 days, together with interannual variations of 1- to 7-year period contribute to the highest extent (about 70%) of the temperature oscillations up to 20 km, changing in both cases the phase in the tropopause region. The other three EOFs indicate prevailing weight of the oscillations in the upper troposphere-low stratosphere region and are characterised by longer periods in both types of fluctuations. The intra-annual variations can be accounted for an interaction between Madden-Julian and Arctic oscillations, while the spectral features of interannual fluctuations could be associated with those of Quasi Biennial, El Niño, and North Atlantic global oscillations.